The school leadership survival guide : what to do when things go wrong, how to learn from mistakes, and why you should prepare for the worst - Brooks, Jeffrey S., 1970-; Heffernan, Amanda (Leadership, schools, and change., 2021)
"The School Leadership Survival Guide: What to Do When Things Go Wrong, How to Learn from Mistakes, and Why You Should Prepare for the Worst is intended as an uncommon guide for school leaders and a resource they can turn to when confronted with issues they might not normally face in typical practice. The book serves as a bridge between research and day-to-day school leadership, and is intended to help leaders and school communities improve in areas they routinely avoid. In this sense, the book is meant as a "go to" resource for principals, those who train and teach them, and scholars. Although authors recognize the complexity of issues raised in the book, each chapter has a "How to" "What to do" or "Why You Should" ethos in order to give the book a unifying structure and help provide a practical translation of research and theory into practice. Some of the issues addressed include: How to elevate student voice; How to navigate religious conflict in the school and community; How to improve support for LGBTIQ students; Why You Should develop a natural disaster plan; How to work against racism in the school and community; How to practice inclusion in the school; How to make a vision and mission come to life; How to manage relationships with difficult people; What to do when there is racial tension in the community; How to learn the history of your school and community-and why that matters; How to guide and support a leadership team, and; What to do in a school with low trust"--